Laboratory screening prior to modified electroconvulsive therapy - Adhikari, S R (Journal of Chitwan Medical College, 2015)
Laboratory screening for subtle medical disease is critical prior to modified electroconvulsive therapy (MECT). It is important to rule out medical condition since MECT is performed under general anesthesia. 25 patients planned for MECT were evaluated with complete blood count, hemoglobin, serum sodium, serum potassium, serum creatinine, blood sugar, electrocardiogram (ECG), chest radiograph (X-ray chest). Investigations showed some abnormal values in blood sugar, serum sodium, serum potassium, ECG and X-ray chest. Proper guideline is needed for evaluation of patients who undergo MECT. Medical conditions along with other subtle diseases are important to rule out before undergoing MECT.